2022
DOI: 10.1038/s41391-022-00554-1
|View full text |Cite
|
Sign up to set email alerts
|

Statins and prostate cancer—hype or hope? The epidemiological perspective

Abstract: Background Men using cholesterol-lowering statin medications have been found to have lower risks of both advanced and fatal prostate cancer in multiple registry-based studies and prospective cohort studies. Statin use has also been associated with longer survival among men already diagnosed with prostate cancer. Mechanisms responsible for purported anti-cancer effects of statins are not well understood but may offer insight into prostate cancer biology. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 74 publications
1
10
0
1
Order By: Relevance
“…This finding is consistent with a study by Craig et al, which reported a 20% reduction in the risk of advanced PCa with statin use. 41 Furthermore, we found that UTIs exhibited a lower risk of PCa and were associated with a higher incidence of BPH (Figure 2).…”
Section: Discussionmentioning
confidence: 82%
“…This finding is consistent with a study by Craig et al, which reported a 20% reduction in the risk of advanced PCa with statin use. 41 Furthermore, we found that UTIs exhibited a lower risk of PCa and were associated with a higher incidence of BPH (Figure 2).…”
Section: Discussionmentioning
confidence: 82%
“…5 6 Numerous epidemiological studies in different cancer types have shown improved survival outcomes in patients taking statins, versus patients not taking these drugs. [7][8][9][10][11][12] In head and neck cancer patients, the use of statins is associated with improved survival outcomes, 11 12 lower incidence of cisplatin-induced hearing loss, 13 and reversal of radiation-induced fibrosis, 14 by mechanisms that are not currently understood. The potential benefit of statins in WHAT IS ALREADY KNOWN ON THIS TOPIC ⇒ Cholesterol may impact antitumor immune responses, and a few prior studies suggest that statin drugs may increase responses to immune checkpoint blockade.…”
Section: Introductionmentioning
confidence: 99%
“…So, it is known that androgen deprivation therapy, the standard treatment for PC, inhibits androgen synthesis in testicles and, consequently, decreases the levels of systemic androgens, but despite the low availability of circulating androgens, tumor progression continues, because there is an intratumoral synthesis of androgens from the existing cholesterol [ 11 ]. Thus, statins are antidyslipidemic drugs that inhibit 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase and block mevalonate production, which is a cholesterol precursor that allows for controlling the synthesis of androgens from cholesterol, which could explain the synergistic effect of statins in androgen deprivation therapy [ 2 , 5 , 10 , 11 ]. On the other hand, it is known that the metabolic pathway of mevalonate is associated with Yes-Associated Protein (YAP) and Tafazzin protein (TAZ), which are related to tumor growth and tumor progression.…”
Section: Pharmacotherapeutic Groups With Potential Efficacy In Pc Tre...mentioning
confidence: 99%
“…Thus, statins will eventually act on both serum cholesterol and intratumoral cholesterol, which is an advantage, because men with high serum cholesterol seem to have a higher risk of developing more aggressive PC and higher mortality rates. On the other hand, significant amounts of statins were detected in the prostate tissue of several patients, which allows us to conclude that statins have a direct effect on prostate cells, and after a four-week treatment with statins, it is already possible to detect them in prostatic tissue [ 11 ].…”
Section: Pharmacotherapeutic Groups With Potential Efficacy In Pc Tre...mentioning
confidence: 99%
See 1 more Smart Citation